Seismic Vulnerability Assessment of Liquid Storage Tanks Isolated by Sliding-Based Systems - Alexandros Tsipianitis; Yiannis Tsompanakis (Advances in Civil Engineering)
Liquid-filled tanks are effective storage infrastructure for water, oil, and liquefied natural gas (LNG). Many such large-scale tanks are located in regions with high seismicity. Therefore, very frequently base isolation technology has to be adopted to reduce the dynamic distress of storage tanks, preventing the structure from typical modes of failure, such as elephant-foot buckling, diamond-shaped buckling, and roof damage caused by liquid sloshing. The cost-effective seismic design of base-isolated liquid storage tanks can be achieved by adopting performance-based design (PBD) principles. In this work, the focus is given on sliding-based systems, namely, single friction pendulum bearings (SFPBs), triple friction pendulum bearings (TFPBs), and mainly on the recently developed quintuple friction pendulum bearings (QFPBs). More specifically, the study is focused on the fragility analysis of tanks isolated by sliding-bearings, emphasizing on isolators’ displacements due to near-fault earthquakes. In addition, a surrogate model has been developed for simulating the dynamic response of the superstructure (tank and liquid content) to achieve an optimal balance between computational efficiency and accuracy.